Random trilinear forms and the Schur multiplication of tensors - Ibrahim Almasri; Jinlu Li; Andrew Tonge (International Journal of Mathematics and Mathematical Sciences)
We obtain estimates for the distribution of the norm of the random trilinear form A:ℓrM×ℓpN×ℓqK→ℂ, defined by A(ei,ej,ek)=aijk, where the aijk's are uniformly bounded, independent, mean zero random variables. As an application, we make progress on the problem when ℓr⊗⌣ℓp⊗⌣ℓq is a Banach algebra under the Schur multiplication.